2022
DOI: 10.1088/1367-2630/ac83e3
|View full text |Cite
|
Sign up to set email alerts
|

Tunable domino effect of thermomagnetic instabilities in superconducting films with multiply-connected topological structures

Abstract: Topology is a crucial ingredient for understanding the physical properties of superconductors. Magnetic field crowds to adopt the form of a topologically-protected quantum flux lines which can lose this property when moving at high velocities. These extreme conditions can be realized when superconductors undergo a thermomagnetic instability for which the sample topology come also into play. In this work, utilizing the magneto-optical imaging technique, we experimentally study magnetic flux avalanches in superc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In this paper, all simulations are implemented using a DC field of this ramp rate. Since the actual electric field can be much larger than that obtained from the simple theoretical calculation due to the strong nonuniformity of the flux penetration both in space and in time, the ramp rates that trigger the thermomagnetic instability are much smaller in experiments [22,34,[55][56][57]. We also show the flux distribution of the films when the magnetic field increases linearly to the same field B a = 8 mT for comparison (see figures 2(d-f)).…”
Section: Resultsmentioning
confidence: 88%
“…In this paper, all simulations are implemented using a DC field of this ramp rate. Since the actual electric field can be much larger than that obtained from the simple theoretical calculation due to the strong nonuniformity of the flux penetration both in space and in time, the ramp rates that trigger the thermomagnetic instability are much smaller in experiments [22,34,[55][56][57]. We also show the flux distribution of the films when the magnetic field increases linearly to the same field B a = 8 mT for comparison (see figures 2(d-f)).…”
Section: Resultsmentioning
confidence: 88%
“…Recent MOI observations and numerical simulations have revealed that random or structured defects significantly affect the TMI behavior of SC thin films [ 25–30 ]. Within inhomogeneous SC films patterned with arrays of antidots [ 25 , 26 , 28 ], blind holes [ 27 , 29 ] and insulating particles [ 30 ], it is found that inhomogeneities strongly modify the current carrying capacity and dramatically change the flux avalanche patterns. Quantitative MOI measurements of the vortex avalanches in SC films show that the probability distributions of avalanche sizes follow power laws and demonstrate finite-size scaling [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%